GENDER AND ECONOMIC ANALYSIS ISSUE IN INDONESIA - Nasrullah Hidayat (Universitas Negeri Medan, 2022)
The purpose of this paper is to study gender and economic analysis issue in Indonesia. Gender analysis provides the basis for carrying out social transformation to realize a new, better life order, through new, more just social relations. The results of this study suggest that In order to support women's empowerment in the economic and labor fields, the following programs were developed: 1) Gender mainstreaming in economic development and employment, 2) Empowering women in the development of the people's economy. Bsides that the ability of women in the field of entrepreneurship, in order to develop productive economic enterprises, increasing women's access to information on natural resources, capital resources, credit and market information, strengthening business partnerships managed by women with the private sector, BUMN, and cooperatives and renewal and improvement of labor laws and regulations for gender equality and justice.Keywords : Gender, Economics, Women